(untitled) (ARQUISUR Revista, 2021)
This article assumes modern architecture as a nodal issue in the conformation of the discipline, still in permanent review and debate[1]. It is proposed to reflect on the materials of the project, understood as the specific resources of a doing, from analyzing and reflecting on the tower building for the Offices for the main headquarters of the soap company, of British origin, “Lever Brother Company ", Known as" Lever House "designed and built by the American architecture studio SOM, during 1951 and 1952, in New York City, at 390 Park Avenue. [1] Ana María Rigotti.